UTILIZATION OF PALM KERNEL SHELL WASTE INTO A BRICKET - Sri Mulyati; Kevin Alvindo; Jubaidi Jubaidi (Proceeding B-ICON, 2023)
Oil palm shell is one of the palm oil processing wastes, which is quite large, reaching 60% of the production of kernel oil. The plantation waste can be processed into an artificial solid fuel which is more widely used as an alternative fuel called bio-briquettes. The researchers aim to utilize palm kernel shell waste (Palm Kernel Shell) into briquettes.This type of research is Quasi Experiment Design with the "Posttest Only Design." In this design, the treatment or intervention has been carried out (X), then measurement (observation) or posttest (O2) is carried out. As long as there is no control group, O2 results are impossible to compare with others. This design is often called "The One Shot Case Study." The results of this observation (O2) only provide descriptive information.The briquettes that have the most prolonged burning power until they turn to ashes, are briquettes with a variation of the adhesive composition of 300 grams, briquettes with good hardiness, namely those using a variation of the adhesive composition of 100 grams, and the results of heating 1 liter of water to a boil, variations of the adhesive composition of 100 grams are used with a faster time than the variation of the adhesive composition of 200 and 300 grams. Communities can use palm shell briquettes as an alternative fuel that can be used for cooking and burning purposes which are environmentally friendly and economical.